2015
DOI: 10.3390/molecules20023027
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibitors of the AAA+ Chaperone p97

Abstract: It is remarkable that a pathway as ubiquitous as protein quality control can be targeted to treat cancer. Bortezomib, an inhibitor of the proteasome, was first approved by the US Food and Drug Administration (FDA) more than 10 years ago to treat refractory myeloma and later extended to lymphoma. Its use has increased the survival rate of myeloma patients by as much as three years. This success was followed with the recent accelerated approval of the natural product derived proteasome inhibitor carfilzomib (Kyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
84
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 112 publications
1
84
0
Order By: Relevance
“…TRIP13 has ATPase activity, and an inactivating mutant of TRIP13 was unable to promote cancer cell invasion, suggesting that the catalytic activity of TRIP13 is essential for cancer progression. Recent studies have reported that small chemical molecules can inhibit the activity of members of the AAA+ family (33). Thus, small chemicals that target TRIP13 may represent a promising drug for the treatment of various types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…TRIP13 has ATPase activity, and an inactivating mutant of TRIP13 was unable to promote cancer cell invasion, suggesting that the catalytic activity of TRIP13 is essential for cancer progression. Recent studies have reported that small chemical molecules can inhibit the activity of members of the AAA+ family (33). Thus, small chemicals that target TRIP13 may represent a promising drug for the treatment of various types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We then used a VCP inhibitor to block its ATPase activity and examined the effect on HCV replication. EerI inhibits VCPdependent ERAD, most likely by irreversibly binding to VCP (44). EerI treatment at 2 M dramatically reduced HCV replication and viral protein levels ( Fig.…”
Section: Tagging Of Hcv Nonstructural Proteins In the Context Of Viramentioning
confidence: 99%
“…p97 hexamers, therefore, are a target for cancer therapies. Small molecules inhibiting p97 ATPase activity have recently been identified24.…”
mentioning
confidence: 99%